A new species of Tree-Snake in the genus Dipsadoboa Günther, 1858 (Squamata : Colubridae : Colubrinae) from West Africa - (:unkn) unknown (My University, 2023)
Since the review of Rasmussen (1993) who restablished Dipsadoboa weileri (Lindholm, 1905) from the synonymy of Dipsadoboa unicolor Günther, 1858, D. weileri is known by three disjunct populations, one with a wide geographic distribution in Central Africa, the second located in mountains of southwestern Togo, the third one distributed in Guinea and Senegal in Fouta Djalon mountains and Mount Nimba. In the present work we attribute the later population to a new species, Dipsadoboa riparia sp. nov., basedon molecular, biogeographic and colour pattern arguments.
Keywords: African Research